Proceedings of 6th Eurasphalt &Amp; Eurobitume Congress 2016
DOI: 10.14311/ee.2016.348
|View full text |Cite
|
Sign up to set email alerts
|

Adjusting design air void Levels in Superpave mixtures to enhance durability

Abstract: When developed in the early 1990s the Superpave method of asphalt design was structured similar to the Marshall method of asphalt design. In the Marshall method asphalt was designed with 3 to 5% air voids (typically 4%). Compaction specifications typically left the mixture with 8% air voids on the road. It was reasoned that traffic would compact the asphalt mixtures and achieve an ultimate density of 96%, the same as the design. Superpave calls for a design air void content of 4.0% (no range) and compaction sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…One obvious, but technically very challenging solution, is to increase the compaction effort in the field to match the design compaction effort required by N design . A much simpler approach is to design more compactable mixtures by choosing an N design value that corresponds to a compaction effort that matches the real compaction effort in the field, as suggested in the Superpave 5 mixture design ( 16 , 17 ). Based on this argument, a method is proposed next to quantify the field compaction effort.…”
Section: Effect Of Ndesign On Field Densitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…One obvious, but technically very challenging solution, is to increase the compaction effort in the field to match the design compaction effort required by N design . A much simpler approach is to design more compactable mixtures by choosing an N design value that corresponds to a compaction effort that matches the real compaction effort in the field, as suggested in the Superpave 5 mixture design ( 16 , 17 ). Based on this argument, a method is proposed next to quantify the field compaction effort.…”
Section: Effect Of Ndesign On Field Densitiesmentioning
confidence: 99%
“…Previous studies have reported on the effect of N design on the compactability of mixtures, and the authors suggested that N design values be adjusted to improve field densities. The best example is the “Superpave 5” mix design method developed by Purdue University, Heritage Research Group, and Indiana DOT ( 16 , 17 ). The N design levels in Superpave 5 were set at 30 and 50 for traffic levels below and above 3 million equivalent single axel loads (ESAL), respectively, values substantially lower compared with the values in the traditional Superpave design method ( 7 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…%Pass of the sieveÀ j %Pass of the sieve on MDLj ð 2Þ This is based on previous research that showed that mixture compactability is related to how close the gradation curve is to MDL (9,10).…”
Section: Aggregate Gradationmentioning
confidence: 99%
“…In this method, N design is related to compaction effort rather than traffic volume, which guarantees consistency between laboratory and field compaction. Superpave 5 mixtures are designed by adjusting aggregate gradation while keeping the effective binder content unchanged, compared with traditional Superpave (9,10).…”
mentioning
confidence: 99%